Patients’ satisfaction with physiotherapy for low back pain among elderly in Institutional care / Hafizah Abdul Aziz - Abdul Aziz, Hafizah (2016)
Background: Patient satisfaction surveys are beneficial to healthcare practitioners as they could be used to find out the quality of care and the treatment given and changes that can be done based on patients’ feedbacks and recommendations. Physiotherapists too have been known to treat elderly with LBP since long ago using different types of approaches in order to reduce physical disability and restore its functions and physiotherapy has been nominated as a beneficial treatment for managing LBP among elderly. Objective: The objectives of this study were (1) to determine the level of satisfaction of elderly with LBP regarding physiotherapy treatment at RSK, (2) to determine the possible relationship between overall satisfaction level with gender and race and (3) to investigate the association between factors affecting satisfaction and satisfaction level itself. Study design: A cross – sectional, descriptive study design. Participant: 80 elderly who received physiotherapy for their LBP in the RSKs (Johor Bharu, Cheng, Taiping and Cheras). Outcome measure: Satisfaction level was measured using Physical Therapy Patient Satisfaction Questionnaire. Result: (1) Overall, 88.8% (n = 71) were highly satisfied with the physiotherapy service and the remaining 11.2% (n = 9) of the participants reported a lower level of satisfaction. Female participants reported high level of satisfaction (53.5%; n = 38) as compared to the male group with only 46.5% (n = 33). Malays reported higher satisfaction level (71.8%;n = 51) as compared to Chinese and Indians with only 28.2% (n = 20) of the reported satisfaction level towards physiotherapy service. (2) No significant association between gender and overall satisfaction level (p = 0.607) and no significant association were found between race and overall satisfaction level (p = 0.095). (3) There was a statistically significant (p < 0.01), positive moderately strong correlation (ρ = +0.768) between patient – physiotherapist interaction factor and overall satisfaction level. There was also a significant positive moderately strong relationship between professionalism of service and overall satisfaction level (p < 0.01; ρ = 0.610). Conclusion: Most of the elderly patients indicated that they achieved high satisfaction level with the physiotherapy service for LBP at RSK and different gender and race do not influence satisfaction level. Plus, from the result, it was best to say that, factors like patient – physiotherapist interaction and professionalism of service greatly influenced the overall level of patients’ satisfaction.